Artificial Intelligence in Emerging Markets : Opportunities, Trends, and Emerging Business Models - International Finance Corporation (International Finance Corporation, Washington, DC, 2021)
Artificial intelligence (AI) - the science of making machines act in rational, intelligent ways is rapidly making inroads into business operations and society. AI is already being applied in many areas of our lives, with high penetration in financial services followed by e-commerce, healthcare, education, agriculture, and manufacturing. Emerging markets can benefit significantly from AI: Its applications are providing new ways to leapfrog infrastructure gaps and solve pressing development challenges in critical sectors. This report explores the latest AI applications and trends in emerging markets and includes several examples of how AI is expanding opportunities and contributing to the achievement of the Sustainable Development Goals. It also sheds light on how investors, clients, and governments can harness its full potential while minimizing its risks, when managed effectively and with safeguards in place, AI can facilitate private investment to reduce poverty and improve lives at a pace inconceivable only a decade ago.